KORELASI SUPERVISI KEPALA MADRASAH TERHADAP KINERJA GURU PENDIDIKAN AGAMA ISLAM DI MADRASAH IBTIDAIYAH ANNIZHOMIYYAH JAHA LABUAN PANDEGLANG BANTEN - Ani Mulyani (UNISAN JURNAL, 2024)
The results of the researcher’s pre-survey, although the head of Madrasah Ibtidaiyah Annizhomiyyah Jaha Labuan Pandeglang Banten has carried out his duties and responsibilities as a supervisor and 88.5% of Islamic Religious Education teachers have been certified, the performance of certified Islamic Religious Education teachers still needs to be improved. For this reason, researchers are interested in conducting further research on "The Influence of Madrasah Head Supervision Management on the Performance of Certified Islamic Religious Education Teachers at Madrasah Ibtidaiyah Annizhomiyyah Jaha Labuan Pandeglang Banten ." The formulation of the research problem is whether there is an influence of madrasa head supervision management on the performance of Islamic Religious Education teachers. who has been certified? The aim of the research is to determine the influence of madrasa head supervisory management on the performance of certified Islamic Religious Education teachers at Madrasah Ibtidaiyah Annizhomiyyah Jaha Labuan Pandeglang Banten . This research uses quantitative methods. The data collection technique used a questionnaire with research respondents of 23 certified Islamic Religious Education teachers. Data analysis uses simple correlation and regression techniques.